2012
DOI: 10.1093/eurheartj/ehs210
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of optimizing prevention in patients with coronary heart disease: the EUROASPIRE III health economics project

Abstract: These results underscore the societal value of optimizing prevention in most patients with established CHD, but also highlight the need for setting priorities towards patients more at risk and the need for more studies comparing intensified prevention with usual care in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 41 publications
2
37
2
Order By: Relevance
“…These results are in line with a simulation study in CAD patients from 8 European countries, which showed that, by optimizing cardiovascular prevention in individuals (smoking cessation, diet and exercise, and better management of SBP and/or LDL‐c), a mean of ≈0.25 QALYs (3 months in perfect health) could be gained 38. The moderate health benefit to be obtained with intensive LLT may be attributable to the higher risk of nonvascular death in this secondary prevention setting, which is not decreased by LLT.…”
Section: Discussionsupporting
confidence: 87%
“…These results are in line with a simulation study in CAD patients from 8 European countries, which showed that, by optimizing cardiovascular prevention in individuals (smoking cessation, diet and exercise, and better management of SBP and/or LDL‐c), a mean of ≈0.25 QALYs (3 months in perfect health) could be gained 38. The moderate health benefit to be obtained with intensive LLT may be attributable to the higher risk of nonvascular death in this secondary prevention setting, which is not decreased by LLT.…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies, such as EUROACTION and Global Secondary Prevention Strategies to Limit (GOSPEL) studies, provided scientific evidence for the beneficial effect and improved prognosis in patients with CHD (25,26). A health economics analysis from EUROASPIRE III showed favorable results with an average incremental cost-effectiveness ratio (ICER) of Euro12,484 per quality-adjusted life year (QALY) (27).…”
Section: Discussionmentioning
confidence: 99%
“…12,13,19 Cholesterol lowering using statins 15,16 and improvement in BP control are cost effective if targeted at persons with high CV risk. 22 Importantly, a sizable portion of patients on lipid-lowering or BP-lowering drug treatment fails to take their treatment adequately or to reach therapeutic goals, 23,24 with clinical and economic consequences.…”
Section: Cost-effectiveness Of Preventionmentioning
confidence: 99%